Factors influencing dividend policy in Vietnamese agricultural enterprises - Linh, Vu Thuy; Hai, Tran Van (Journal of Social Economics Research, 2025)
The agricultural sector has long played an important role in the economic development of each country, especially for an economy like Vietnam. Considered one of the key sectors, the role of the agricultural sector is not only reflected in providing food for society but also as a driving force for the strong development of many other economic sectors. This study focuses on analyzing the factors influencing dividend policy among agricultural companies in Vietnam. Based on survey data from 130 firms in the sector and employing an empirical approach using a multiple regression model, the research develops an analytical framework consisting of five key factors: profitability, investment strategy, corporate governance structure, business environment, and industry characteristics. The findings indicate that profitability has a positive impact on dividend policy, while investment strategy exerts a negative influence, as firms tend to retain earnings for expansion purposes. Corporate governance and the business environment show a positive effect, highlighting the role of transparent management and stable external conditions in shaping dividend policy. Meanwhile, the volatile nature of the agricultural industry places pressure on dividend payout decisions. The results not only reinforce the scientific basis for formulating dividend policies tailored to the specific features of the agricultural sector but also provide practical insights for business managers, investors, and policymakers in guiding development strategies, attracting capital, and enhancing the credibility of Vietnamese agricultural firms in an increasingly integrated global economy.